Problems of counterfeiting medical products in Ukraine - Аркуша, Лариса Ігорівна; Аркуша, Л. І.; Аркуша, Лариса Игоревна; Arkusha, Larysa I.; Гловюк, Ірина Василівна; Гловюк, І. В.; Гловюк, Ирина Васильевна; Hloviuk, Iryna V.; Завальнюк, Сергій Володимирович; Завальнюк, С. В.; Завальнюк, Сергей Владимирович; Zavalniuk, Serhii V. (ALUNA Publishing, 2019)
Objective: Introduction: The provision of medical products of adequate quality should be considered as constituent element of the human right to life, inextricably linked with the right to health care protection and medical care. However, the Ukrainian market of counterfeit medical products affects the guaranteeing of the right to health care protection and medical care in Ukraine. The current situation necessitates a study of the legal regulation of counterfeiting of medical products in Ukraine and an increase in its effectiveness. The aim of the research is the formation of scientifically based approaches to improve the activities on counterfeiting of medical products in Ukraine in the aspect of normative regulation. Patients and methods: Materials and methods: The empirical base of the research is the national legislation of Ukraine, data from the General Prosecutor's Office of Ukraine and the Unified State Register of Court Decisions. The methodological basis is a set of general and special research methods of scientific cognition, namely: the logical and normative method; statistical method, as well as methods of comparative analysis and logical methods of research. Results: Review: In the course of the research, the authors have analyzed international acts, national legislation of Ukraine determining the directions and specific features of the activities of state agencies in counterfeiting of medical products in Ukraine, the data of the General Prosecutor's Office of Ukraine and the Unified State Register of Court Decisions. On the basis of the performed analysis, the authors have suggested measures aimed at increasing the effectiveness of counterfeiting of medical products. Conclusion: Conclusions: The imperfection of the existing system of counterfeiting of medical products in Ukraine has been proven. The authors have offered organizational measures to increase the effectiveness of counterfeiting of medical products, as well as to amend the current criminal, criminal and procedural legislation, taking into account the MEDICRIME Convention ratified in Ukraine.

Мета: Вступ: Забезпечення медичними товарами належної якості слід розглядати як складову частину права людини на життя, нерозривно пов'язану з правом на охорону здоров'я та медичне обслуговування. Проте український ринок контрафактної медичної продукції впливає на гарантування права на охорону здоров’я та медичне обслуговування в Україні. Ситуація, що склалася, зумовлює необхідність вивчення правового регулювання фальсифікації медичних товарів в Україні та підвищення її ефективності. Метою дослідження є формування науково обґрунтованих підходів до удосконалення діяльності з фальсифікації медичних товарів в Україні в аспекті нормативного регулювання. Пацієнти та методи: Матеріали та методи: Емпіричною базою дослідження є національне законодавство України, дані Генеральної прокуратури України та Єдиного державного реєстру судових рішень. Методологічною основою є сукупність загальних і спеціальних методів дослідження наукового пізнання, а саме: логіко-нормативний метод; статистичний метод, а також методи порівняльного аналізу та логічні методи дослідження. Результати: Огляд: У ході дослідження авторами проаналізовано міжнародні акти, національне законодавство України, що визначає напрями та особливості діяльності державних органів з фальсифікації медичних виробів в Україні, дані Генеральної прокуратури України. Україна та Єдиний державний реєстр судових рішень. На основі проведеного аналізу автори запропонували заходи, спрямовані на підвищення ефективності фальсифікації медичних товарів. Висновок: Висновки: Доведено недосконалість існуючої в Україні системи контрафактної продукції медичного призначення. Авторами запропоновано організаційні заходи щодо підвищення ефективності фальсифікації медичних товарів, а також внесення змін до чинного кримінального, кримінального та процесуального законодавства з урахуванням ратифікованої в Україні Конвенції MEDICRIME.
Arkusha L. I. Problems of counterfeiting medical products in Ukraine / L. I. Arkusha, I. V. Hloviuk, S. V. Zavalniuk // Wiadomosci lekarskie (Warsaw, Poland : 1960). - № 72 (5 cz 2). - ALUNA Publishing, 2019. - P. 1131-1135.
Keywords: counteraction; damage reimbursement; falsification; investigation; medical products; протидія; відшкодування збитків; фальсифікація; розслідування; медичні вироби; Research Subject Categories::LAW/JURISPRUDENCE